Peran Pendidikan Akhlak dalam Menumbuhkan Kesehatan Mental Siswa di MA Takhassus al-Qur’an 1 Mojotengah Wonosobo - Nala Fury Ashlah; Robingun Suyud El Syam; Muhtar Sofwan Hidayat (Lembaga Yasin AlSys, 2026)
Previous research on moral education and mental health has been dominated by quantitative approaches, so it has not fully described the process of internalizing moral values and students’ subjective experiences in depth. This study aims to describe students’ mental health conditions, analyze the role of moral education in fostering mental health, and identify supporting and inhibiting factors in its implementation at MA Takhassus Al-Qur’an 1 Mojotengah Wonosobo. This study used a qualitative approach with a field research design, involving the principal, the akidah akhlak teacher, the guidance and counseling teacher, and Grade XI students selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that most students had fairly good mental health conditions, characterized by adaptability, positive social relationships, and active involvement in madrasah activities, although some students still experienced anxiety, lack of self-confidence, and difficulty controlling their emotions. Moral education played an important role through classroom learning, teacher role modeling, and religious habituation in helping students control their emotions, build inner calm, and strengthen character. Supporting factors in the implementation of moral education included the pesantren environment, rural community culture, a culture of tawaduk, and a religious school environment, whereas inhibiting factors included a lack of family support, the influence of negative peer environments, and the absence of a specific mental health program. The conclusion of this study emphasizes the importance of integrating moral education with structured mental health services so that students’ psychological needs can be addressed more optimally. These findings contribute to strengthening the literature on moral education and mental health and provide practical implications for madrasahs in designing character development programs integrated with professional psychological support.